Comportamiento ante cargas cíclicas del reforzamiento de uniones viga-columna de concreto reforzado construidas antes del código de 1984 utilizando CFRP (2017)
In Colombia, there are a lot of buildings designed without seismic recommendations, which were implemented in 1984 with the arrival of the first building code to the country. The use of carbon fibers for the reinforcement of existing buildings has come in growth in Colombia. However, its implementation in the retrofitting of beam-column joints has been minimal, due to the little information about the behavior of these materials as seismic reinforcement of joints, as well as the lack of a clear procedure for the structural design for this reinforcement alternative. In this document are exposed the results of an investigation project where different retrofitting alternatives using polymers reinforced by carbon fibers (CFRP) where evaluated, through pseudo dynamic tests over four (4) beam-column joints built to 1:1 scale. The results showed the feasibility of executing reinforcement of beam-column joints that were designed without taking into account the seismic recommendations by using CRFP, reaching similar behaviors than one specimen built following the requirements of the NSR-10 building code. In addition, it was proved that the flexural capacity of the beam and column can be improved by placing carbon fiber cords through the joint.